Makna Melambaikan Tangan sebagai Komunikasi Nonverbal Pengendara Vespa - Zayyan Risqullah; Vera Wijayanti Sutjipto (GLOBAL SCIENTS PUBLISHER, 2026)
Waving is often considered a simple gesture, but this is not the case for Vespa riders. This gesture has a deep meaning, as shown in the video “Utamakan Saling Tegur Sapa” on the DDS VVLOG YouTube channel, where Vespa riders' wave to each other as a way of greeting one another on the road. This study uses Roland Barthes' semiotic approach, which reads signs on three levels: denotation, connotation, and myth. The results of the study show that denotatively, waving is a body movement to greet other riders. Connotatively, this gesture carries a message of brotherhood, respect, and togetherness within the Vespa community. Mythically, waving one's hand shapes the image of Vespa riders as a group with a distinctive lifestyle that upholds freedom of expression, uniqueness, and the romanticism of classic culture inherent in the Vespa identity. Therefore, waving one's hand is not only a simple form of greeting but also a medium of nonverbal communication that strengthens solidarity, fosters a sense of togetherness, and reinforces group identity. The contribution of this research lies in enriching the study of nonverbal communication in the context of the Vespa community, which has rarely been researched, while also presenting a novelty in the form of an analysis of the digital representation of Vespa cultural practices on social media.